Uji Coba Pemadatan Bahan Timbunan Inti Kedap Air bendungan Batutegi - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran (UI2P2) Universitas Gadjah Mada, 2003)
Trial embankment test for embankment darn shall be carried out prior the construction of the dam in order to setup the embankment rule that will be adopted during construction of the darn. Trial embankment was carried out in order to ensure that the compaction results meet the requirements. This paper described the trial embankment test for core materials at Batutegi dam, a rockfill darn with 125 meter in height above their foundation in Lampung, Indonesia. The 2 type of compactor, there are 20 tons double drum static padfoot roller and 15 tons single drum padfoot vibratory roller were selected for trial. Determination of layer thickness, number of passes and other engineering aspects are discussed. The results indicated that both compactors produced the similar number of passes to produce the acceptable degree of compaction, but the double drum static padfoot roller have a better capacity due to the greater layer thickness